EFEKTIVITAS PENGGUNAAN MEDIA SOSIAL (@jktinfo) DALAM MEMENUHI KEBUTUHAN INFORMASI FOLLOWERS - Aulia Syahfitriani; Iflah Iflah (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
The development of digital technology changes a lot of things, one thing that change is communication. At this time digital communication made a lot of social media applications, like instagram. Instagram is a social media that can be used to gain such as information, like @jktinfo is one of account that share's a lot of information like traffic way, culinary, weather condition, and updated news around DKI Jakarta. The purpose of this research is assessing stage of effectiveness @jktinfo Instagram account on fulfilling the followers information needs that can be assessed with six different stages such as receiver, content, timing, format, media and source. This type of research is a quantitative descriptive, the population are collected from the followers of @jktinfo's Instagram account and 100 people were chosen as samples with convenience sampling as the sampling technique. All the data are convened by online survey with questionnaire. The results of this study showed that Instagram account @jktinfo is highly effective for fulfilling the followers information needs with a percentage above 81%.